Treatment through a preoperative anemia clinic is associated with a reduction in perioperative red blood cell transfusion in patients undergoing orthopedic and gynecologic surgery. Issue 4 (11th March 2022) - Guinn, Nicole R.; Fuller, Matt; Murray, Sutton; Aronson, Solomon; ,
Abstract: Background: Preoperative anemia is associated with increased morbidity, mortality, and risk of transfusion. Treatment through a preoperative anemia clinic (PAC) may improve outcomes. Study Design and Methods: Adult patients undergoing elective orthopedic and gynecologic surgery with preoperative anemia were identified and referred for hemoglobin optimization with iron and/or erythropoietin from a single‐site academic health center. Treated patients were propensity matched to untreated controls and compared on outcomes of erythrocyte transfusion, length of stay (LOS), and readmission. Changes in hemoglobin relative to treatment time before surgery were also measured in the treated cohort. Results: One thousand three hundred thirty‐two patients were evaluated between July 2015 and March 2021, of which 161 underwent optimization through the PAC. After propensity matching, 127 (98 orthopedic and 29 gynecology) PAC‐treated patients were compared to 127 (98 orthopedic and 29 gynecology) control patients who did not undergo treatment. The primary outcome of perioperative transfusion was significantly lower in treated patients compared with matched controls (12.60% vs. 26.77%, p = .005). A lower LOS was demonstrated in the gynecologic PAC subgroup (2.2 [1.5, 2.4] vs. 3.1 [2.2, 3.4], p = .002). Each day of treatment time before surgery was associated with an increase of 0.040 g/dL hemoglobin ( p < .001) until 65 days, after which further time did not increase hemoglobin. Conclusion: Treatment through a preoperative anemia clinic is associated with a reduction in perioperative transfusion and possible reduction in LOS and readmission compared with matched controls. Additionally, treatment time before surgery is correlated with a greater increase in hemoglobin up until 2 months prior to surgery.